Optimization of SnS active layer thickness for solar cell application. (November 2017) - Gupta, Yashika; Arun, P.
Abstract: This work presents a comparative study of n-SnS and p-SnS active layers for increased solar cell efficiency. Tin sulphide thin films of various thicknesses having p-type and n-type conductivity were fabricated by thermal evaporation. Both type of films had the same (113) orientation of the crystal planes with a constant tensile strain of 0.003 and 0.011, respectively. The persistent photocurrent was observed in all n-SnS and p-SnS samples with the current's time decay constant decreasing with increasing film thickness. Hole mobility of thicker p-SnS films was found to be greater than the electron mobility in n-SnS samples, with mobility (both hole and electron) showing an increasing trend with film thickness. The optimum absorber layer thickness for both p- and n-SnS layers should have a high value of diffusion length for a given absorption coefficient and band-gap.